Reaction of methyl fluoroformyl peroxycarbonate (FC(O)OOC(O)OCH3) with Cl atoms: Formation of hydro-chlorofluoro-peroxides - Berasategui, Matias (2017)
The products following Cl atom initiated reactions of FC(O)OOC(O)OCH3 in 50-760 Torr of N2 at 296 K were investigated using FTIR. Reaction of Cl atoms with methyl fluoroformyl peroxycarbonate proceeds mainly via attack at the methyl group, forming FC(O)OOC(O)OCH2 • radicals. Further reaction of this kind of radical with Cl2 forms three new compounds: FC(O)OOC(O)OCH2Cl, FC(O)OOC(O)OCHCl2, and FC(O)OOC(O)OCCl3, whose existence was characterized experimentally by FTIR spectroscopy assisted by ab initio calculations at the B3LYP/6-31++G(d,p) level. Relative rate techniques were used to measure k(Cl+FC(O)OOC(O)OCH3) = (4.0 ± 0.4) × 10-14 cm3 molecule-1 s-1 and k(Cl+FC(O)OOC(O)OCH2Cl) = (3.2 ± 0.3) × 10-14 cm3 molecule-1 s-1. When the reaction is run in the presence of oxygen, the paths giving chlorinated peroxide formation are suppressed, and oxidation to (mainly) CO2 and HCl takes place through highly oxidized intermediates with lifetimes long enough to be detected by FTIR spectroscopy.